Unraveling the mechanism of cascade reactions of zincke aldehydes - Paton, Robert S; Steinhardt, Sarah E; Vanderwal, Christopher D; Houk, K N (Journal of the American Chemical Society, 2011)
The thermal pericyclic cascade rearrangement of Zincke aldehydes (5-(dialkylamino)-2,4-pentadienals) to afford Z-α,β,γ,δ-unsaturated amides discovered by the Vanderwal group has been studied in depth using quantum mechanical methods. Two mechanistic possibilities that had previously been put forth to explain this internal redox process, one that had been discounted by experiment and the other that had withstood experimental scrutiny, were evaluated. Both of these mechanisms suffered from energetic barriers that appeared too high to allow rearrangement to proceed under the conditions used; however, computational study of a third possibility that implicates the intermediacy of vinylketenes revealed that it is the most likely pathway of rearrangement. Further computational studies accounted for the relative rates of rearrangement in substituted Zincke aldehydes, predicted the feasibility of related processes for other donor-acceptor dienes, and provided insight into the rearrangement of allylamine-derived Zincke aldehydes that provide either dihydropyridones or polycyclic lactams by further pericyclic processes.